Analysis of The Socio-Economic Impact of Alfamidi's Existence on Grocery Stores in Heram District, Jayapura City - Lazarus Ramandei; Sudiro Sudiro; Juliani Wairata (Mandalika Institute, 2025)
This study examines the socio-economic impact of Alfamidi minimarkets on traditional grocery stores in Heram District, Jayapura City. Using mixed methods including surveys, interviews, and Geographic Information System (GIS) analysis, the research analyzed distribution patterns and competitive dynamics between modern and traditional retail. Results reveal a uniform distribution pattern of Alfamidi outlets strategically positioned near arterial roads, providing competitive advantages through modern facilities and digital services. This has resulted in up to 30% revenue decline for traditional grocery stores. The study employs SWOT analysis to identify challenges and opportunities, recommending zoning regulations and business collaboration to maintain local economic sustainability. The findings contribute to understanding retail transformation dynamics in developing urban areas and highlight the need for balanced economic growth strategies.